Writing Awig-Awig Pangkungkarung Gede Traditional Village, Tabanan, Bali - I Ketut Sukadana; Ni Made Jaya Senastri; Luh Putu Suryani; I Made Yudhiantara; Mahadewi Mulia Gangga; Dewa Ayu Adhika Saraswati (Community Service Journal of Law, 2024)
The situation at the Mitra location does not yet have awig-awig as mandated by Bali Provincial Regulation Number 4 of 2019. The aim of this program is to empower the Traditional Village community so that they have a rule in the form of awig-awig. The method used in this service program is by: (1) giving lectures or legal counseling about the importance of awig-awig in life in Traditional Villages, (2) carrying out focus group discussions (FGD) about the design of awig-awig, and (3) provide assistance in the preparation of awig-awig of Traditional Villages. The results of this program activity are the formation of an awig-awig with a total of 59 Pawos (articles).